Pengaruh Good Governance Dan Standar Akuntansi Pemerintah Terhadap Kualitas Laporan Keuangan Pada Pemerintah Daerah Kabupaten Jombang - Dewi Nita Rahmawati; Hadi Sucipto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research seeks to examine how the application of Good Governance principles and adherence to Government Accounting Standards influence the quality of financial reports within the Jombang Regency Government. A quantitative research design was adopted, utilizing a survey method through the distribution of questionnaires to officials responsible for financial management in Regional Apparatus Organizations. The study involved 56 purposively selected respondents. Data were processed through descriptive statistics, validity and reliability assessments, classical assumption testing, and multiple linear regression analysis using SPSS software. Findings reveal that both Good Governance practices and Government Accounting Standards individually exert a positive and significant impact on the quality of local government financial statements. Among these, Government Accounting Standards emerge as the most influential factor affecting financial report quality. The study concludes that enhancing the quality of local government financial reporting necessitates a collaborative effort between robust governance implementation and consistent adherence to accounting standards, reinforcing the principle of public financial accountability.